Overlap Syndrome Between Sjögren's Syndrome and Systemic Sclerosis - Alejandro Londoño Amariles; Bryam Fernando Holguín Muñoz; Lina María Saldarriaga Rivera (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Overlap syndrome is a condition in which a patient experiences symptoms that correspond to two or more of these classification standards. More commonly, the overlap is limited to one or more manifestations of each disease. Sjögren's syndrome is a systemic autoimmune disease characterized by the presence of a dry syndrome, primarily xerostomia and xerophthalmia, originating from dysfunction of exocrine glands. Conversely, systemic sclerosis is a rare autoimmune disease characterized by fibrosis development in the skin, internal organs, and vasculopathies. THE CASE: Our case report presents a 62-year-old woman with a history of Sjögren's syndrome, who exhibited symptoms of xerostomia, xerophthalmia, xerodermia, and had anti-Ro antibodies exceeding 200, along with ultrasound findings of chronic sialadenitis. The patient was under treatment with hydroxychloroquine, pilocarpine, and deflazacort. She attended the rheumatology outpatient clinic for routine follow-up of her disease. During the evaluation, bilateral sclerodactyly and "salt and pepper" lesions on the limbs were observed, along with two reports of ANA with titers of 1:2650 and a centromere pattern. Due to suspicion of coexistence of limited systemic sclerosis, anticentromere antibodies were requested, yielding a positive result, while anti-Scl 70 antibodies were negative. This confirmed the diagnostic suspicion, and azathioprine 50 mg every 12 hours and colchicine 0.5 mg daily were added to her therapy. CONCLUSION: Although Sjögren's syndrome and systemic sclerosis can manifest independently, in certain instances, both conditions overlap. It is worth noting that among the various overlap syndromes related to connective tissue diseases, this overlap is infrequent. However, within connective tissue diseases, systemic sclerosis tends to exhibit overlap more frequently, reported in up to 20-30% of cases. In cases of connective tissue diseases, consideration should always be given to overlap syndromes, involving a meticulous physical examination and careful assessment of laboratory results to avoid overlooking conditions that may negatively impact patients' future quality of life.